REMITTANCES AND ECONOMIC GROWTH: AN EMPIRICAL ANALYSIS FROM NIGERIA - Ahmed Oluwatobi ADEKUNLE (International Journal of Social and Educational Innovation)
This paper examines the nexus amid remittances and economic growth in Nigeria. The paper employed ARDL techniques to evaluate the time-series data covering 1986-2021 sourced from World Development Indicator (WDI, 2021). The findings show that 1% increase in remittances would result in a 0.32% increase in GDP over the long term, according to our model's results, which provide support for the "view upheld by contemporary development financial analysts that international remittance inflows are one of the major macroeconomic factors that significantly promote long-run economic growth in globalized countries. One possible policy conclusion from this study is that Nigeria can boost its economic growth performance by encouraging remittances and exchange rate stability as well as investing in more conventional growth sources like foreign direct investment (FDI), since the study found that FDI is one of the key factors that can spur growth in Nigeria